General mechanisms of coagulation and targets of anticoagulants (Section I) - De Caterina, Raffaele; Husted, Steen; Wallentin, Lars; Andreotti, Felicita; Arnesen, Harald; Bachmann, Fedor; Baigent, Colin; Huber, Kurt; Jespersen, Jørgen; Kristensen, Steen Dalby; Lip, Gregory Y. H.; Morais, João; Rasmussen, Lars Hvilsted; Siegbahn, Agneta; Verheugt, Freek W. A.; Weitz, Jeffrey I. (Thrombosis and Haemostasis, 2013)
Contrary to previous models based on plasma, coagulation processes are currently believed to be mostly cell surface-based, including three overlapping phases: initiation, when tissue factor-expressing cells and microparticles are exposed to plasma; amplification, whereby small amounts of thrombin induce platelet activation and aggregation, and promote activation of factors (F)V, FVIII and FXI on platelet surfaces; and propagation, in which the Xase (tenase) and prothrombinase complexes are formed, producing a burst of thrombin and the cleavage of fibrinogen to fibrin. Thrombin exerts a number of additional biological actions, including platelet activation, amplification and self-inhibition of coagulation, clot stabilisation and anti-fibrinolysis, in processes occurring in the proximity of vessel injury, tightly regulated by a series of inhibitory mechanisms. ″Classical″ anticoagulants, including heparin and vitamin K antagonists, typically target multiple coagulation steps. A number of new anticoagulants, already developed or under development, target specific steps in the process, inhibiting a single coagulation factor or mimicking natural coagulation inhibitors.
Keywords: Anticoagulants; coagulation; tissue factor; heart disease; coronary heart disease; heart failure; atrial fibrillation